STUDI LITERATUR: ANALISIS PENGGUNAAN MEDIA AUDIO VISUAL PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Muhamad Seto Satriyo; Putri Monika Syari; Desti Pratiwi; Episiasi (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This study is a literature review that examines the use of audio-visual media in Social Studies learning at the elementary school level. The purpose of this research is to analyze the role of audio-visual media in attracting students’ attention, supporting understanding of learning materials, and improving learning outcomes. The method used is a literature study by collecting data from journals, books, and relevant scientific sources published in recent years. The data analyzed consist of secondary data using a descriptive qualitative approach. The findings show that audio-visual media can increase students’ interest and learning motivation, facilitate understanding of abstract concepts, and have a positive impact on students’ learning outcomes. Audio-visual media also create more concrete and meaningful learning experiences through visual and auditory presentation. However, several obstacles were identified, including limited facilities, technical problems, and teachers’ low ability in operating the media. Therefore, institutional support and teacher training are needed to optimize the use of audio-visual media in Social Studies learning.